2014
DOI: 10.1111/j.1600-048x.2013.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Avian malaria is associated with increased reproductive investment in the blue tit

Abstract: Haemosporidians causing avian malaria are very common parasites among bird species. Their negative effects have been repeatedly reported in terms of deterioration in survival prospects or reproductive success. However, a positive association between blood parasites and avian fitness has also been reported. Here, we studied a relationship between presence of malaria parasites and reproductive performance of the host, a hole-breeding passerine -the blue tit Cyanistes caeruleus. Since the malaria parasites might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…), geographic population (Rebar and Greenfield ), clutch size (Podmokła et al. ), food availability (Krams et al. ), and paternity assurance (Benowitz et al.…”
Section: Discussionmentioning
confidence: 99%
“…), geographic population (Rebar and Greenfield ), clutch size (Podmokła et al. ), food availability (Krams et al. ), and paternity assurance (Benowitz et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is often found that two unrelated host species sharing an environment, are infected by the same parasite lineage, indicating that lineages can cross host species boundaries (Ricklefs andFallon 2002, Bensch et al 2007). Notably, hosts infected by haemosporidia blood parasites can still reproduce successfully even though these parasites can effect host survival (Asghar et al 2015) and fitness in multiple ways (Lachish et al 2011), and no effect , negative effects (Knowles et al 2009, Lachish et al 2011) and positive effects (Podmokła et al 2014) on host fitness have been reported. Notably, hosts infected by haemosporidia blood parasites can still reproduce successfully even though these parasites can effect host survival (Asghar et al 2015) and fitness in multiple ways (Lachish et al 2011), and no effect , negative effects (Knowles et al 2009, Lachish et al 2011) and positive effects (Podmokła et al 2014) on host fitness have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…They can have devastating impacts in naïve populations (Atkinson & Samuel, 2010), and many studies have reported negative associations with infection in endemic areas, including reductions in condition (Marzal, Bensch, Reviriego, Balbontin, & de Lope, 2008;Merino, Moreno, Sanz, & Arriero, 2000), antipredator behavior (Garcia-Longoria, Moller, Balbontin, de Lope, & Marzal, 2015;Mukhin et al, 2016), mating display behavior (Bosholn, Fecchio, Silveira, Braga, & Anciaes, 2016), survival (Asghar et al, 2015;Krams et al, 2013;Sol, Jovani, & Torres, 2003), and reproductive output (Asghar, Hasselquist, & Bensch, 2011;Knowles, Palinauskas, & Sheldon, 2010;Marzal et al, 2013;Merino et al, 2000). Other studies, however, have reported no associations-or even positive associations-with infection (Cornelius, Davis, & Altizer, 2014;Fargallo & Merino, 2004;Piersma & van der Velde, 2012;Podmokla et al, 2014;Zylberberg et al, 2015), or have reported effects that vary among host species (Atkinson & Van Riper, 1991;Ellis, Kunkel, & Ricklefs, 2014;Sorci, 2013), host population (Piersma & van der Velde, 2012), parasite species (Asghar et al, 2011;Lachish, Knowles, Alves, Wood, & Sheldon, 2011;Marzal et al, 2008), and characteristics of individual hosts (Hammers et al, 2016). As such, the extent to which the hemosporidians broadly constitute a selective pressure across different systems and contexts is unclear.…”
Section: Introductionmentioning
confidence: 99%